Open University Center of the Pontifical Javeriana University, Colombia - Parra de Marroquin, Omayra; Claricia Corredor Moyano, Lina (International Review of Research in Open and Distributed Learning, 2002)
According to García Canclini (1990) there is the assumption that Colombia is a hybrid society. Upon this standpoint, and within a traditional higher education structure characterized by being fundamentally conventional or campus based, the Open University Center of the Pontificia Universidad Javeriana was created as an education program that breaks with every traditional scheme, which in turn, encourages a new learning pattern. The Open University Center emerges as a "social response" focused on the "here and now" of today's society in Colombia.The Javeriana University (a hybrid university) can be placed in this context as well as the Open University Center, as a part of it. Since its creation, through its programs this center offers education to the most vulnerable of Colombia's population, contributing to raise their quality of life.In this article, the authors outline the Open University Center's place in the University's context: its historical development and its structure concerning students, programs, regulations, infrastructure and technological equipment. They also identify the implications and relationships of the traditional education proper of the Pontificia Universidad Javeriana, as well as the projection and contributions of the Open University Center to the University's future in the pedagogical order of distance education towards virtual education.